2004
DOI: 10.1213/01.ane.0000131964.67524.e7
|View full text |Cite
|
Sign up to set email alerts
|

Capnography Accurately Detects Apnea During Monitored Anesthesia Care

Abstract: Apnea and airway obstruction are common during monitored anesthesia care (MAC). Because their early detection is essential, we sought to measure the efficacy of capnography as an indicator of apnea during MAC at a variety of oxygen flow rates compared with thoracic impedance. Anesthesia care providers using standard American Society of Anesthesiologists monitors were blinded to capnography and thoracic impedance monitoring. Ten (26%) of the 39 patients studied developed 20 s of apnea; none was detected by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
72
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(76 citation statements)
references
References 17 publications
0
72
0
4
Order By: Relevance
“…In an effort to identify all such cases, we used an SaO 2 of ≤90% at any stage during the procedure as indication of respiratory depression, while other authors used this saturation level for at least 30 seconds as a definition of desaturation. 29 Soto and colleagues 30 showed that apnea of >20 seconds occurred in 26% of the PSAs performed in their study, all of which were diagnosed by capnography. None were detected by the provider monitoring the patient.…”
Section: Limitationsmentioning
confidence: 85%
See 1 more Smart Citation
“…In an effort to identify all such cases, we used an SaO 2 of ≤90% at any stage during the procedure as indication of respiratory depression, while other authors used this saturation level for at least 30 seconds as a definition of desaturation. 29 Soto and colleagues 30 showed that apnea of >20 seconds occurred in 26% of the PSAs performed in their study, all of which were diagnosed by capnography. None were detected by the provider monitoring the patient.…”
Section: Limitationsmentioning
confidence: 85%
“…None were detected by the provider monitoring the patient. 30 While recognizing apnea is important, reacting to very brief periods identified with capnography could induce caregivers to use positive pressure ventilation before oxygen desaturation, which could actually increase the danger of aspiration. If brief apnea was missed in some of our patients, the universally good outcome in our series suggests that detecting such apnea is probably unnecessary.…”
Section: Limitationsmentioning
confidence: 99%
“…[17] Although the jury is still out regarding whether ETC improves patient safety during PSA, there is less of a doubt that apnea is common during the process and that ETC does detect this earlier than PO alone. Soto et al [5] showed that apnea of greater than 20 seconds occurred in 26% (10 of 39) cases of monitored anesthesia care/ sedation, all of whom were diagnosed by capnography, while none was detected by the provider monitoring the patient. Miner et al [1] found that in 74 patients undergoing PSA, 33 were diagnosed with RD, all of whom met the ETC criteria for RD, yet only 11 (33%) were detected by PO.…”
Section: Discussionmentioning
confidence: 99%
“…The standards are less categorical about the use of ETC in the ED because of the lack of evidence supporting its use. [3,5,6] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation